A colorful mobile phone back cover based on fiber cloth and its preparation process

Through the combination of modified fiber cloth and self-repaired polyurethane prepolymer, combined with composite nanofiber crystals and photocuring technology, the problems of insufficient signal reception, puncture resistance and aesthetics of existing mobile phone back cover materials are solved, and impact resistance and heat dissipation are achieved , self-healing and colorful appearance of the phone back cover.

CN118322667BActive Publication Date: 2025-02-18HUIZHOU ZONGSHENG ELECTRONICS MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410343214.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2025-02-18
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

Existing mobile phone back cover materials such as carbon fiber have problems affecting signal reception. The glass fiber cloth has poor puncture resistance and heat dissipation, and its appearance is single and its aesthetics are insufficient.

Method used

Using a colorful mobile phone back cover preparation process based on fiber cloth, the modified fiber cloth is modified through plasma treatment and vinyl polyborosiloxane precursor body fluid treatment, combined with self-healing polyurethane prepolymer and composite nanofiber crystals, photocuring treatment and The hollow design forms a colorful mobile phone back cover that is impact-resistant and heat-dissipated.

Benefits of technology

It achieves strong impact resistance and good heat dissipation of the back cover of the mobile phone, has a self-repair and superhydrophobic surface, and has a colorful appearance, which improves the aesthetics and performance of the mobile phone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004757534500000101
    Figure BDA0004757534500000101
  • Figure BDA0004757534500000111
    Figure BDA0004757534500000111
Patent Text Reader

Abstract

The invention relates to the field of mobile phones, in particular to a colorful mobile phone back cover based on fiber cloth and a preparation process thereof. The fiber cloth is subjected to plasma treatment and vinyl polyborosiloxane precursor liquid treatment to form vinyl polyborosiloxane on the surface of the fiber cloth; hydroxyl-terminated polydimethylsiloxane, polytetrahydrofuran and isophorone diisocyanate are used as raw materials, and a polyurethane prepolymer is prepared under the catalytic condition of dibutyltin dilaurate; bis(2-hydroxyethyl) disulfide is used as a chain extender, and acryl glycinamide is used as a capping agent; a self-repairing polyurethane prepolymer is used as a protective coating base material, and composite nano fiber crystals are introduced as fillers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of mobile phones, in particular to a colorful mobile phone back cover based on fiber cloth and a preparation process thereof. Background Art

[0002] With the rapid development of society, consumers have put forward new requirements for the functions and appearance of electronic products such as mobile phones. With the development of thinner and lighter electronic products, how to use high-strength and lightweight materials such as glass fiber and carbon fiber to prepare the back cover of mobile phones has become an existing research hotspot.

[0003] There is a problem of affecting the signal reception of the mobile phone when using carbon fiber as raw material to prepare the mobile phone back cover. Although glass fiber will not affect the signal reception, the glass fiber cloth in the mobile phone back cover in the existing market is mostly single-layered, which has problems with puncture resistance and poor heat dissipation. Usually, a large amount of inorganic filler is filled to improve the heat dissipation of the mobile phone back cover, but at the same time it also causes its impact resistance to decrease; and the existing mobile phone back covers are mostly monochrome in appearance, with single display effects and content, which reduces the aesthetics of the mobile phone. Summary of the invention

[0004] The purpose of the present invention is to provide a colorful mobile phone back cover based on fiber cloth and a preparation process thereof, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A preparation process of a colorful mobile phone back cover based on fiber cloth comprises the following steps:

[0007] S1: sequentially subjecting the fiber cloth to plasma treatment and vinyl polyborosiloxane precursor liquid treatment to obtain a modified fiber cloth;

[0008] S2: mixing the self-repairing polyurethane prepolymer and the photoinitiator in the dark to obtain a dipping solution;

[0009] S3: putting the modified fiber cloth into the dipping solution, stacking, and once light-curing to obtain a semi-cured composite board;

[0010] S4: milling the semi-cured composite board and opening a hollow position corresponding to the position of the mobile phone signal device to obtain a base material layer;

[0011] S5: mixing the self-repairing polyurethane prepolymer, the composite nanofiber crystal, and the photoinitiator in a dark environment to obtain a protective coating;

[0012] S6: Compounding the substrate layer, the base layer, the colorful layer, and the optical coating layer in sequence, and then coating the protective coating, performing secondary photocuring treatment to form a protective layer, and performing low-temperature curing treatment to obtain a colorful mobile phone back cover based on fiber cloth.

[0013] Furthermore, the fiber cloth is one of glass fiber cloth, carbon fiber cloth, basalt fiber cloth and aramid fiber cloth.

[0014] Furthermore, the working conditions of the plasma treatment are: power of 150 W, time of 1-2 min, and working gas of oxygen.

[0015] Furthermore, the vinyl polyborosiloxane precursor liquid treatment includes the following steps: mixing vinyl-terminated dimethyl polysiloxane and boric acid, and keeping the mixture at 68-72° C. for 18-22 minutes to obtain a vinyl polyborosiloxane precursor liquid; placing the pretreated fiber cloth in the vinyl polyborosiloxane precursor liquid and ultrasonically treating the mixture for 10-20 minutes, heating the mixture to 165-175° C. and keeping the mixture for 2 hours, cooling, and drying the mixture to obtain a modified fiber cloth.

[0016] Furthermore, the working conditions of the primary photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm for 65-75s; the working conditions of the secondary photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm for 10-12s; and the working conditions of the low-temperature curing treatment are: keeping warm at 85-95℃ for 2-3h.

[0017] Furthermore, the composition of the dipping solution, in parts by mass, is: 22-28 parts of self-healing polyurethane prepolymer, 0.1-0.3 parts of photoinitiator; the composition of the protective coating, in parts by mass, is: 25-35 parts of self-healing polyurethane prepolymer, 1-3 parts of composite nanofiber crystals, 0.2-0.5 parts of photoinitiator; the composition of the colorful layer, in parts by mass, is: 10-13 parts of dipping solution, 1-2 parts of pigment.

[0018] Furthermore, the optical coating layer is an indium tin oxide layer, which is prepared by an evaporation process or a sputtering process. The parameters of the sputtering process are: the target material is an indium tin oxide target material, the gas pressure is 3 Pa, and the power is 2 W / cm 2 The working gas is a mixture of argon and oxygen with a volume ratio of 20:1.

[0019] An optical coating layer is added behind the colorful layer to give the back cover of the mobile phone a colorful effect, greatly improving the aesthetics of the back cover of the mobile phone.

[0020] Furthermore, the photoinitiator is one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone.

[0021] Furthermore, the preparation of the self-healing polyurethane prepolymer includes the following steps: under a nitrogen atmosphere, hydroxyl-terminated polydimethylsiloxane, polytetrahydrofuran, and isophorone diisocyanate are mixed, a mixed solution of N,N-dimethylformamide and dibutyltin dilaurate is added, and the mixture is kept warm at 78-82°C for 100-120 minutes to obtain a prepolymer; the prepolymer is cooled to 58-62°C, bis(2-hydroxyethyl) disulfide and acetone are added, and the mixture is kept warm for 50-60 minutes, a mixed solution of acrylylglycinamide and N,N-dimethylformamide is added, and stirring is continued for 1-2 hours, and the material is discharged to obtain a self-healing polyurethane prepolymer.

[0022] Furthermore, the preparation of the composite nanofiber crystal includes the following steps:

[0023] (1) Mixing nanocellulose and sodium periodate solution under light-proof conditions, adjusting the pH to 4, keeping the mixture at 38-42° C. for 2-3 hours, adding ethylene glycol, adjusting the pH to 8, continuing to stir for 20-30 minutes, dialyzing to neutrality, rotary evaporation, and freeze-drying to obtain dialdehyde nanocellulose;

[0024] (2) Mixing dialdehyde-modified nanocellulose, acrylyl glycinamide, and deionized water, heating to 38-42° C. and stirring for 8-10 min, adding dimethyl sulfoxide, continuing stirring for 5-6 h, adding sodium borohydride until there are no bubbles, washing with ethanol 3-5 times, dialyzing to neutrality, rotary evaporation, and freeze-drying to obtain an intermediate preparation;

[0025] (3) The intermediate preparation, N,N-dimethylacetamide and anhydrous pyridine are mixed, the temperature is raised to 48-52°C, stearoyl chloride is added, the temperature is kept for 3-4 hours, the mixture is dispersed in ethanol and stirred, centrifuged for 8-10 minutes, washed with tetrahydrofuran for 3-5 times, and dried to obtain composite nanofiber crystals.

[0026] Furthermore, the preparation of acryloyl glycinamide includes the following steps: under a nitrogen atmosphere, glycinamide hydrochloride and ice water are mixed, ice ether and ice potassium carbonate solution are added, ether and acryloyl chloride are added, the temperature is raised to 18-25°C and kept warm for 1-2 hours, the pH is adjusted to 1.9-2.1, the aqueous phase is washed with ether 3-5 times, the pH is adjusted to neutral, rotary evaporation, freeze drying, washing, rotary evaporation, drying, adding a mixed solution of ethanol and methanol in a volume ratio of 4:1, heating to 145°C, recrystallization, and acryloyl glycinamide is obtained.

[0027] Beneficial effects of the present invention:

[0028] The invention provides a colorful mobile phone back cover based on fiber cloth and a preparation process thereof, and adopts light curing treatment to prepare a mobile phone back cover with strong impact resistance, good heat dissipation and a self-repairing super-hydrophobic surface.

[0029] The fiber cloth is treated with plasma to improve its surface activity and the bonding strength between the fiber cloth and the vinyl polyborosiloxane precursor liquid. Vinyl polyborosiloxane is formed on the surface of the fiber cloth by the reaction of vinyl-terminated dimethyl polysiloxane and boric acid. This improves the mechanical strength of the fiber cloth and gives the surface of the fiber cloth carbon-carbon double bonds. Under the influence of a photoinitiator, the fiber cloth undergoes free radical polymerization with a self-healing polyurethane prepolymer containing carbon-carbon double bonds in the dipping solution, thereby improving the bonding strength between the dipping solution and the fiber cloth and giving the fiber cloth a self-healing surface.

[0030] In order to improve the mechanical damage resistance and aging resistance of the back cover of the mobile phone, hydroxyl-terminated polydimethylsiloxane, polytetrahydrofuran and isophorone diisocyanate were used as raw materials and a polyurethane prepolymer was prepared under the catalytic condition of dibutyltin dilaurate. Bis(2-hydroxyethyl) disulfide was used as a chain extender to introduce disulfide bonds into the polyurethane, which together with the hydrogen bonds in the self-healing polyurethane prepolymer gave the self-healing polyurethane prepolymer self-healing property. Acryloyl glycinamide was used as a capping agent to introduce amide bonds and double bonds into the self-healing polyurethane prepolymer, so that free radical polymerization occurred under the influence of a photoinitiator, thereby improving the compatibility between the modified fiber cloth and the dipping solution and improving the impact resistance and puncture resistance of the back cover of the mobile phone.

[0031] A hollow position is opened on the base material layer of the back cover of the mobile phone at a position corresponding to the position of the mobile phone signal device to improve its ability to receive signals, and a light-curing base layer is added between the base material layer and the colorful layer to avoid the influence of the fiber cloth weaving texture on the subsequent colorful layer.

[0032] In order to improve the UV aging resistance and heat dissipation of the back cover of the mobile phone, self-healing polyurethane prepolymer is used as the base material of the protective coating, and nanofiber crystals are introduced as fillers. In order to improve the uniformity of the dispersion of nanofiber crystals in the protective coating, the nanofiber crystals are modified and the nanocellulose is treated with sodium periodate to obtain dialdehyde nanocellulose. The aldehyde-amino reaction is used to graft acryloyl glycinamide on the surface of the nanocellulose to give the nanocellulose carbon-carbon double bonds, thereby improving the bonding strength between the nanocellulose and the self-healing polyurethane prepolymer, so that it can achieve a permanent non-falling effect. The hydroxyl groups on the surface of the nanocellulose are used to graft stearyl chloride to improve the hydrophobicity of the nanocellulose, further improving the hydrophobicity of the protective layer and giving it a super hydrophobic surface. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0035] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0036] Embodiment 1: A process for preparing a colorful mobile phone back cover based on fiber cloth, comprising the following steps:

[0037] S1: sequentially subjecting the fiber cloth to plasma treatment and vinyl polyborosiloxane precursor liquid treatment to obtain a modified fiber cloth; the fiber cloth is a glass fiber cloth;

[0038] The working conditions of plasma treatment were: power 150 W, time 1 min, and working gas oxygen;

[0039] The vinyl polyborosiloxane precursor liquid treatment comprises the following steps: 1 mmol of vinyl-terminated dimethyl polysiloxane and 0.8 mmol of boric acid are mixed and kept at 68° C. for 22 minutes to obtain a vinyl polyborosiloxane precursor liquid; 2 g of pretreated fiber cloth is placed in 5 g of the vinyl polyborosiloxane precursor liquid and subjected to ultrasonic treatment for 10 minutes, the temperature is raised to 165° C. and kept for 2 hours, cooled, and dried to obtain a modified fiber cloth;

[0040] S2: By weight, 22 parts of self-repairing polyurethane prepolymer and 0.1 parts of photoinitiator were mixed evenly in the dark to obtain a dipping solution;

[0041] The preparation of the self-healing polyurethane prepolymer comprises the following steps:

[0042] Under a nitrogen atmosphere, 2 g of hydroxyl-terminated polydimethylsiloxane, 12 g of polytetrahydrofuran, and 8 g of isophorone diisocyanate were mixed, and a mixed solution of 6 mL of N, N-dimethylformamide and 36 mg of dibutyltin dilaurate was added, and the mixture was kept warm at 78 ° C for 120 min to obtain a prepolymer; the prepolymer was cooled to 58 ° C, 1.04 mmol of bis (2-hydroxyethyl) disulfide and 4 mL of acetone were added, and the mixture was kept warm for 50 min, and a mixed solution of 256 mg of acrylyl glycinamide and 10 mL of N, N-dimethylformamide was added, and the mixture was stirred for 1 h, and the material was discharged to obtain a self-healing polyurethane prepolymer;

[0043] S3: putting the modified fiber cloth into the dipping solution, stacking, and once light-curing to obtain a semi-cured composite board;

[0044] The working conditions of the primary light curing treatment are: using ultraviolet light with a wavelength of 365nm and a time of 65s;

[0045] S4: milling the semi-cured composite board, opening a hollow position corresponding to the position of the mobile phone signal equipment, and obtaining a base material layer;

[0046] S5: By weight, 25 parts of self-repairing polyurethane prepolymer, 1 part of composite nanofiber crystal, and 0.2 parts of photoinitiator are mixed evenly in the dark to obtain a protective coating;

[0047] The preparation of composite nanofiber crystals includes the following steps:

[0048] (1) Under light-proof conditions, 4 g of nanocellulose and 120 mL of 0.5 mol / L sodium periodate solution were mixed, the pH was adjusted to 4, and the mixture was kept at 38° C. for 3 h. 4.5 mL of ethylene glycol was added to adjust the pH to 8. The mixture was stirred for 20 min, and the mixture was poured into a dialysis bag with a molecular weight of 3500 and dialyzed to neutrality. The mixture was then rotary evaporated and freeze-dried to obtain dialdehyde-modified nanocellulose.

[0049] (2) 4 g of dialdehyde-modified nanocellulose, 18 g of acryloyl glycinamide, and 400 mL of deionized water were mixed, heated to 38 °C and stirred for 10 min, 2.5 mL of dimethyl sulfoxide was added, and stirring was continued for 5 h. 2.5 g of sodium borohydride was added until there were no bubbles, washed with ethanol three times, dialyzed to neutrality, rotary evaporated, and freeze-dried to obtain an intermediate preparation;

[0050] (3) 1 g of the intermediate preparation, 30 mL of N,N-dimethylacetamide, and 5 mL of anhydrous pyridine were mixed, the temperature was raised to 48°C, 3.2 mL of stearoyl chloride was added, and the mixture was kept warm for 3 h, and then dispersed in 95% ethanol, stirred, centrifuged for 8 min, washed 3 times with tetrahydrofuran, and dried to obtain composite nanofiber crystals;

[0051] S6: Compounding the substrate layer, the primer layer, the colorful layer, and the optical coating layer in sequence, and then coating the protective coating, performing secondary photocuring to form a protective layer, and performing low-temperature curing to obtain a colorful mobile phone back cover based on fiber cloth;

[0052] The composition of the primer layer is 10 parts of the dipping solution and 1 part of the pigment a by weight, and the primer layer is formed by photocuring treatment, and the conditions of the photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm for 5s; the composition of the multi-colored layer is 10 parts of the dipping solution and 1 part of the pigment b by weight, and the multi-colored layer is formed by photocuring treatment, and the conditions of the photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm for 10s;

[0053] The optical coating layer is an indium tin oxide layer, which is prepared by a sputtering process. The parameters of the sputtering process are: the target material is an indium tin oxide target material, the gas pressure is 3Pa, and the power is 2W / cm 2 , the working gas is a mixture of argon and oxygen with a volume ratio of 20:1;

[0054] The working conditions of secondary light curing treatment are: using ultraviolet light with a wavelength of 365nm for 10s; the working conditions of low-temperature curing treatment are: keeping warm at 85℃ for 3h;

[0055] The preparation of acryloyl glycinamide includes the following steps: under a nitrogen atmosphere, 2.1 g of glycinamide hydrochloride and 2 mL of ice water are mixed, 3 mL of ice ether and 11.2 mL of 2 mol / L ice potassium carbonate solution are added, 8 mL of ether and 1.9 g of acryloyl chloride are added, the temperature is raised to 18°C ​​and kept for 2 hours, the pH is adjusted to 1.9, the aqueous phase is washed with ether for 3 times, the pH is adjusted to neutral, rotary evaporation is performed, freeze drying is performed, washing is performed, rotary evaporation is performed, drying is performed, 50 mL of a mixed solution of ethanol and methanol in a volume ratio of 4:1 is added, the temperature is raised to 145°C, and recrystallization is performed to obtain acryloyl glycinamide.

[0056] Embodiment 2: A process for preparing a colorful mobile phone back cover based on fiber cloth, comprising the following steps:

[0057] S1: sequentially subjecting the fiber cloth to plasma treatment and vinyl polyborosiloxane precursor liquid treatment to obtain a modified fiber cloth; the fiber cloth is a glass fiber cloth;

[0058] The working conditions of plasma treatment were: power 150 W, time 1.5 min, working gas oxygen;

[0059] The vinyl polyborosiloxane precursor liquid treatment comprises the following steps: 1 mmol of vinyl-terminated dimethyl polysiloxane and 0.8 mmol of boric acid are mixed and kept at 70° C. for 20 minutes to obtain a vinyl polyborosiloxane precursor liquid; 2 g of pretreated fiber cloth is placed in 5 g of the vinyl polyborosiloxane precursor liquid and subjected to ultrasonic treatment for 15 minutes, the temperature is raised to 170° C. and kept for 2 hours, cooled, and dried to obtain a modified fiber cloth;

[0060] S2: By weight, 25 parts of self-repairing polyurethane prepolymer and 0.2 parts of photoinitiator were mixed evenly in the dark to obtain a dipping solution;

[0061] The preparation of the self-healing polyurethane prepolymer comprises the following steps:

[0062] Under a nitrogen atmosphere, 2 g of hydroxyl-terminated polydimethylsiloxane, 12 g of polytetrahydrofuran, and 8 g of isophorone diisocyanate were mixed, and a mixed solution of 6 mL of N, N-dimethylformamide and 36 mg of dibutyltin dilaurate was added, and the mixture was kept warm at 80 ° C for 110 min to obtain a prepolymer; the prepolymer was cooled to 60 ° C, 1.04 mmol of bis (2-hydroxyethyl) disulfide and 4 mL of acetone were added, and the mixture was kept warm for 55 min, and a mixed solution of 256 mg of acrylyl glycinamide and 10 mL of N, N-dimethylformamide was added, and stirring was continued for 1.5 h, and the material was discharged to obtain a self-healing polyurethane prepolymer;

[0063] S3: putting the modified fiber cloth into the dipping solution, stacking, and once light-curing to obtain a semi-cured composite board;

[0064] The working conditions of the primary light curing treatment are: using ultraviolet light with a wavelength of 365nm and a time of 70s;

[0065] S4: milling the semi-cured composite board, opening a hollow position corresponding to the position of the mobile phone signal equipment, and obtaining a base material layer;

[0066] S5: By weight, 28 parts of self-repairing polyurethane prepolymer, 2 parts of composite nanofiber crystals, and 0.3 parts of photoinitiator were mixed evenly in the dark to obtain a protective coating;

[0067] The preparation of composite nanofiber crystals includes the following steps:

[0068] (1) Under light-proof conditions, 4 g of nanocellulose and 120 mL of 0.5 mol / L sodium periodate solution were mixed, the pH was adjusted to 4, and the mixture was kept at 40° C. for 2.5 h. 4.5 mL of ethylene glycol was added, the pH was adjusted to 8, and the mixture was stirred for 25 min. The mixture was poured into a dialysis bag with a molecular weight of 3500 and dialyzed to neutrality. The mixture was then rotary evaporated and freeze-dried to obtain dialdehyde-modified nanocellulose.

[0069] (2) 4 g of dialdehyde-modified nanocellulose, 18 g of acryloyl glycinamide, and 400 mL of deionized water were mixed, heated to 40 °C and stirred for 9 min, 2.5 mL of dimethyl sulfoxide was added, stirring was continued for 5.5 h, 2.5 g of sodium borohydride was added until there were no bubbles, washed with ethanol 4 times, dialyzed to neutrality, rotary evaporated, and freeze-dried to obtain an intermediate preparation;

[0070] (3) 1 g of the intermediate preparation, 30 mL of N,N-dimethylacetamide, and 5 mL of anhydrous pyridine were mixed, the temperature was raised to 50°C, 3.2 mL of stearoyl chloride was added, and the mixture was kept warm for 3.5 h, and then dispersed in 95% ethanol with a mass concentration of 95%, stirred, centrifuged for 9 min, washed with tetrahydrofuran 4 times, and dried to obtain composite nanofiber crystals;

[0071] S6: Compounding the substrate layer, the primer layer, the colorful layer, and the optical coating layer in sequence, and then coating the protective coating, performing secondary photocuring to form a protective layer, and performing low-temperature curing to obtain a colorful mobile phone back cover based on fiber cloth;

[0072] The composition of the primer layer is 10 parts of dipping solution and 1 part of pigment a by weight, and the primer layer is formed by photocuring treatment, and the conditions of the photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm for 5s; the composition of the multi-colored layer is 11 parts of dipping solution and 1.5 parts of pigment b by weight, and the multi-colored layer is formed by photocuring treatment, and the conditions of the photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm for 11s;

[0073] The optical coating layer is an indium tin oxide layer, which is prepared by a sputtering process. The parameters of the sputtering process are: the target material is an indium tin oxide target material, the gas pressure is 3Pa, and the power is 2W / cm 2 , the working gas is a mixture of argon and oxygen with a volume ratio of 20:1;

[0074] The working conditions of secondary light curing treatment are: using ultraviolet light with a wavelength of 365nm for 13s; the working conditions of low-temperature curing treatment are: keeping warm at 90℃ for 2.5h;

[0075] The preparation of acryloyl glycinamide includes the following steps: under a nitrogen atmosphere, 2.1 g of glycinamide hydrochloride and 2 mL of ice water are mixed, 3 mL of ice ether and 11.2 mL of 2 mol / L ice potassium carbonate solution are added, 8 mL of ether and 1.9 g of acryloyl chloride are added, the temperature is raised to 20°C and kept warm for 1.5 hours, the pH is adjusted to 2, the aqueous phase is washed with ether for 4 times, the pH is adjusted to neutral, rotary evaporation is performed, freeze drying is performed, washing is performed, rotary evaporation is performed, drying is performed, 50 mL of a mixed solution of ethanol and methanol in a volume ratio of 4:1 is added, the temperature is raised to 145°C, and recrystallization is performed to obtain acryloyl glycinamide.

[0076] Embodiment 3: A process for preparing a colorful mobile phone back cover based on fiber cloth, comprising the following steps:

[0077] S1: sequentially subjecting the fiber cloth to plasma treatment and vinyl polyborosiloxane precursor liquid treatment to obtain a modified fiber cloth; the fiber cloth is a glass fiber cloth;

[0078] The working conditions of plasma treatment were: power 150 W, time 2 min, and working gas oxygen;

[0079] The vinyl polyborosiloxane precursor liquid treatment comprises the following steps: 1 mmol of vinyl-terminated dimethyl polysiloxane and 0.8 mmol of boric acid are mixed and kept at 72° C. for 18 minutes to obtain a vinyl polyborosiloxane precursor liquid; 2 g of pretreated fiber cloth is placed in 5 g of the vinyl polyborosiloxane precursor liquid and subjected to ultrasonic treatment for 20 minutes, the temperature is raised to 175° C. and kept for 2 hours, cooled, and dried to obtain a modified fiber cloth;

[0080] S2: By weight, 28 parts of self-repairing polyurethane prepolymer and 0.3 parts of photoinitiator were mixed evenly in the dark to obtain a dipping solution;

[0081] The preparation of the self-healing polyurethane prepolymer comprises the following steps:

[0082] Under a nitrogen atmosphere, 2 g of hydroxyl-terminated polydimethylsiloxane, 12 g of polytetrahydrofuran, and 8 g of isophorone diisocyanate were mixed, and a mixed solution of 6 mL of N, N-dimethylformamide and 36 mg of dibutyltin dilaurate was added, and the mixture was kept warm at 82°C for 100 min to obtain a prepolymer; the prepolymer was cooled to 62°C, 1.04 mmol of bis(2-hydroxyethyl) disulfide and 4 mL of acetone were added, and the mixture was kept warm for 60 min, and a mixed solution of 256 mg of acrylylglycinamide and 10 mL of N, N-dimethylformamide was added, and stirring was continued for 2 h, and the material was discharged to obtain a self-healing polyurethane prepolymer;

[0083] S3: putting the modified fiber cloth into the dipping solution, stacking, and once light-curing to obtain a semi-cured composite board;

[0084] The working conditions of the primary light curing treatment are: using ultraviolet light with a wavelength of 365nm and a time of 75s;

[0085] S4: milling the semi-cured composite board, opening a hollow position corresponding to the position of the mobile phone signal equipment, and obtaining a base material layer;

[0086] S5: By weight, 35 parts of self-repairing polyurethane prepolymer, 3 parts of composite nanofiber crystals, and 0.5 parts of photoinitiator were mixed evenly in the dark to obtain a protective coating;

[0087] The preparation of composite nanofiber crystals includes the following steps:

[0088] (1) Under light-proof conditions, 4 g of nanocellulose and 120 mL of 0.5 mol / L sodium periodate solution were mixed, the pH was adjusted to 4, and the mixture was kept at 42° C. for 2 h. 4.5 mL of ethylene glycol was added to adjust the pH to 8. The mixture was stirred for 30 min, and then the mixture was poured into a dialysis bag with a molecular weight of 3500 and dialyzed to neutrality. The mixture was then rotary evaporated and freeze-dried to obtain dialdehyde-modified nanocellulose.

[0089] (2) 4 g of dialdehyde-modified nanocellulose, 18 g of acryloyl glycinamide, and 400 mL of deionized water were mixed, heated to 42 °C and stirred for 8 min, 2.5 mL of dimethyl sulfoxide was added, stirring was continued for 6 h, 2.5 g of sodium borohydride was added until there were no bubbles, washed with ethanol 5 times, dialyzed to neutral, rotary evaporated, and freeze-dried to obtain an intermediate preparation;

[0090] (3) 1 g of the intermediate preparation, 30 mL of N,N-dimethylacetamide, and 5 mL of anhydrous pyridine were mixed, the temperature was raised to 52°C, 3.2 mL of stearoyl chloride was added, and the mixture was kept warm for 4 h, and then dispersed in 95% ethanol, stirred, centrifuged for 10 min, washed with tetrahydrofuran 5 times, and dried to obtain composite nanofiber crystals;

[0091] S6: Compounding the substrate layer, the primer layer, the colorful layer, and the optical coating layer in sequence, and then coating the protective coating, performing secondary photocuring to form a protective layer, and performing low-temperature curing to obtain a colorful mobile phone back cover based on fiber cloth;

[0092] The composition of the primer layer is 10 parts of dipping solution and 1 part of pigment a by weight, and the primer layer is formed by photocuring treatment, and the conditions of the photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm and the time is 5s; the composition of the multi-colored layer is 13 parts of dipping solution and 2 parts of pigment b by weight, and the multi-colored layer is formed by photocuring treatment, and the conditions of the photocuring treatment are: selecting ultraviolet light with a wavelength of 365nm and the time is 12s;

[0093] The optical coating layer is an indium tin oxide layer, which is prepared by a sputtering process. The parameters of the sputtering process are: the target material is an indium tin oxide target material, the gas pressure is 3Pa, and the power is 2W / cm 2 , the working gas is a mixture of argon and oxygen with a volume ratio of 20:1;

[0094] The working conditions of secondary light curing treatment are: using ultraviolet light with a wavelength of 365nm for 15s; the working conditions of low-temperature curing treatment are: keeping warm at 95℃ for 2h;

[0095] The preparation of acryloyl glycinamide includes the following steps: under a nitrogen atmosphere, 2.1 g of glycinamide hydrochloride and 2 mL of ice water are mixed, 3 mL of ice ether and 11.2 mL of 2 mol / L ice potassium carbonate solution are added, 8 mL of ether and 1.9 g of acryloyl chloride are added, the temperature is raised to 25°C and kept for 1 hour, the pH is adjusted to 2.1, the aqueous phase is washed with ether 5 times, the pH is adjusted to neutral, rotary evaporation is performed, freeze drying is performed, washing is performed, rotary evaporation is performed, drying is performed, 50 mL of a mixed solution of ethanol and methanol in a volume ratio of 4:1 is added, the temperature is raised to 145°C, and recrystallization is performed to obtain acryloyl glycinamide.

[0096] Comparative Example 1: Example 3 was used as a control group, and no vinyl polyborosiloxane precursor liquid treatment was performed, and other processes were normal.

[0097] Comparative Example 2: Taking Example 3 as the control group, nanocellulose was used to replace the composite nanofiber crystal, and other processes were normal.

[0098] Comparative Example 3: Taking Example 3 as the control group, the intermediate preparation was used to replace the composite nanofiber crystal, and the other processes were normal.

[0099] In the embodiments and comparative examples, the thickness of the substrate layer is 0.2 mm, the thickness of the primer layer is 20 μm, the thickness of the multi-color layer is 30 μm, the thickness of the optical coating layer is 20 nm, and the thickness of the protective layer is 40 μm.

[0100] Source of raw materials (for demonstration only):

[0101] Glass fiber cloth 106: China Jushi Group Co., Ltd.; Photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone) 405655: Sigma-Aldrich (Shanghai) Trading Co., Ltd.; Nanocellulose: Jinjinle Chemical Co., Ltd.; Vinyl-terminated dimethyl polysiloxane V304361, boric acid B111592, hydroxy-terminated polydimethylsiloxane P433351, pigment aC139969, pigment bP341831, polytetrahydrofuran P118599, isophorone diisocyanate I109582, N, N-Dimethylformamide D111999, dibutyltin dilaurate D100274, bis(2-hydroxyethyl) disulfide B598951, sodium periodate S616472, ethylene glycol E103319, dimethyl sulfoxide D103272, anhydrous pyridine P111513, stearoyl chloride S101680, tetrahydrofuran T431413, glycinamide hydrochloride G106202, acryloyl chloride A104614: Aladdin reagent; ether, glacial potassium carbonate, sodium borohydride, acetone, ethanol, methanol, analytical grade: Sinopharm reagent.

[0102] Performance test: The performance test was performed on the mobile phone back covers obtained in the embodiments and comparative examples:

[0103] Impact strength: Tested with reference to GB / T1843-2008, sample size is 85mm×15mm, impact energy is 5.5J; Water contact angle: Tested with 2μL deionized water droplets; Heat dissipation: Tested with reference to ASTMD5470, thermal conductivity tested with a thermal conductivity tester, sample size is 80mm×20mm; Self-healing property: Scratch with a length of 100μm, a width of 2μm, and a depth of 30μm was made on the surface, kept at 50℃ for 12h, and the initial scratch length L0 and the scratch length L1 after keeping warm were recorded, self-healing rate = (L0-L1) / L0×100%, the results are shown in Table 1 below;

[0104] Table 1

[0105]

[0106]

[0107] The present invention provides a colorful mobile phone back cover based on fiber cloth and a preparation process thereof. A photocuring treatment is adopted to prepare a mobile phone back cover with strong impact resistance, good heat dissipation and a self-repairing super-hydrophobic surface. In Table 1, / indicates that the item has not been tested.

[0108] Example 3 is compared with Comparative Example 1, and the fiber cloth is treated with plasma to improve the surface activity of the fiber cloth and improve the bonding strength between the fiber cloth and the vinyl polyborosiloxane precursor liquid. Vinyl polyborosiloxane is formed on the surface of the fiber cloth by the reaction of vinyl-terminated dimethyl polysiloxane and boric acid. While improving the mechanical strength of the fiber cloth, the surface of the fiber cloth is given carbon-carbon double bonds, so that free radical polymerization occurs with the self-healing polyurethane prepolymer containing carbon-carbon double bonds in the dipping solution under the presence of a photoinitiator, thereby improving the bonding strength between the dipping solution and the fiber cloth and giving the fiber cloth a self-healing surface.

[0109] Example 3 is compared with Comparative Examples 2 and 3. In order to improve the UV aging resistance and heat dissipation of the back cover of the mobile phone, a self-repairing polyurethane prepolymer is used as a protective coating base material, and nanofiber crystals are introduced as fillers. In order to improve the uniformity of dispersion of the nanofiber crystals in the protective coating, the nanofiber crystals are modified, and the nanocellulose is treated with sodium periodate to obtain dialdehyde-modified nanocellulose. The aldehyde-amino reaction is used to graft acryloyl glycinamide on the surface of the nanocellulose to give the nanocellulose carbon-carbon double bonds, thereby improving the bonding strength between the nanocellulose and the self-repairing polyurethane prepolymer, so that it can achieve a permanent non-falling effect. The hydroxyl groups on the surface of the nanocellulose are used to graft stearyl chloride to improve the hydrophobicity of the nanocellulose, further improve the hydrophobicity of the protective layer, and give it a super hydrophobic surface.

[0110] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A process for preparing a colorful mobile phone back cover based on fiber cloth, characterized in that: The following steps are involved: S1: sequentially subjecting the fiber cloth to plasma treatment and vinyl polyborosiloxane precursor liquid treatment to obtain a modified fiber cloth; S2: mixing the self-repairing polyurethane prepolymer and the photoinitiator in the dark to obtain a dipping solution; S3: putting the modified fiber cloth into the dipping solution, stacking, and once light-curing to obtain a semi-cured composite board; S4: milling the semi-cured composite board and opening a hollow position corresponding to the position of the mobile phone signal device to obtain a base material layer; S5: mixing the self-repairing polyurethane prepolymer, the composite nanofiber crystal, and the photoinitiator in a dark environment to obtain a protective coating; S6: Compounding the substrate layer, the primer layer, the colorful layer, and the optical coating layer in sequence, and then coating the protective coating, performing secondary photocuring to form a protective layer, and performing low-temperature curing to obtain a colorful mobile phone back cover based on fiber cloth; The vinyl polyborosiloxane precursor liquid treatment comprises the following steps: vinyl-terminated dimethyl polysiloxane and boric acid are mixed, and the mixture is kept warm at 68-72° C. for 18-22 minutes to obtain a vinyl polyborosiloxane precursor liquid; the pretreated fiber cloth is placed in the vinyl polyborosiloxane precursor liquid for ultrasonic treatment for 10-20 minutes, the temperature is raised to 165-175° C. and kept warm for 2 hours, cooled, and dried to obtain a modified fiber cloth; The preparation of the self-healing polyurethane prepolymer comprises the following steps: In a nitrogen atmosphere, hydroxyl-terminated polydimethylsiloxane, polytetrahydrofuran and isophorone diisocyanate are mixed, a mixed solution of N,N-dimethylformamide and dibutyltin dilaurate is added, and the mixture is kept at 78-82°C for 100-120 minutes to obtain a prepolymer; the prepolymer is cooled to 58-62°C, bis(2-hydroxyethyl) disulfide and acetone are added, and the mixture is kept warm for 50-60 minutes, a mixed solution of acrylyl glycinamide and N,N-dimethylformamide is added, and the mixture is stirred for 1-2 hours, and the mixture is discharged to obtain a self-healing polyurethane prepolymer; The preparation of composite nanofiber crystals includes the following steps: (1) In the dark, nanocellulose and sodium periodate solution are mixed, the pH is adjusted to 4, and the mixture is kept at 38-42°C for 2-3 hours. Ethylene glycol is added to adjust the pH to 8, and the mixture is stirred for 20-30 minutes. The mixture is dialyzed to neutrality, and then subjected to rotary evaporation and freeze drying to obtain dialdehyde nanocellulose. (2) Mix dialdehyde-modified nanocellulose, acrylyl glycinamide, and deionized water, heat to 38-42°C, stir for 8-10 minutes, add dimethyl sulfoxide, continue stirring for 5-6 hours, add sodium borohydride until there are no bubbles, wash with ethanol 3-5 times, dialyze until neutral, rotary evaporate, and freeze-dry to obtain an intermediate preparation; (3) Mix the intermediate preparation, N,N-dimethylacetamide and anhydrous pyridine, heat to 48-52°C, add stearyl chloride, keep warm for 3-4 hours, disperse in ethanol, stir, centrifuge for 8-10 minutes, wash with tetrahydrofuran for 3-5 times, and dry to obtain composite nanofiber crystals; The preparation of acryloyl glycinamide comprises the following steps: under a nitrogen atmosphere, mixing glycinamide hydrochloride and ice water, adding ice ether and ice potassium carbonate solution, adding ether and acryloyl chloride, heating to 18-25°C and keeping warm for 1-2 hours, adjusting the pH to 1.9-2.1, washing the aqueous phase with ether for 3-5 times, adjusting the pH to neutral, rotary evaporation, freeze drying, washing, rotary evaporation, drying, adding a mixed solution of ethanol and methanol in a volume ratio of 4:1, heating to 145°C, recrystallizing, and obtaining acryloyl glycinamide.

2. The process for preparing a colorful mobile phone back cover based on fiber cloth according to claim 1, characterized in that: The fiber cloth is one of glass fiber cloth, carbon fiber cloth, basalt fiber cloth and aramid fiber cloth; the working conditions of plasma treatment are: power is 150W, time is 1-2min, and working gas is oxygen.

3. The process for preparing a colorful mobile phone back cover based on fiber cloth according to claim 1, characterized in that: The optical coating layer is an indium tin oxide layer, and the indium tin oxide layer is prepared by an evaporation process or a sputtering process.

4. The process for preparing a colorful mobile phone back cover based on fiber cloth according to claim 1, characterized in that: The working conditions for the primary light curing treatment are: using ultraviolet light with a wavelength of 365nm for 65-75s; the working conditions for the secondary light curing treatment are: using ultraviolet light with a wavelength of 365nm for 10-12s; the working conditions for the low-temperature curing treatment are: keeping warm at 85-95℃ for 2-3h.

5. The process for preparing a colorful mobile phone back cover based on fiber cloth according to claim 1, characterized in that: The composition of the dipping solution is, by weight, 22-28 parts of self-repairing polyurethane prepolymer and 0.1-0.3 parts of photoinitiator; the composition of the protective coating is, by weight, 25-35 parts of self-repairing polyurethane prepolymer, 1-3 parts of composite nanofiber crystals and 0.2-0.5 parts of photoinitiator; the composition of the colorful layer is, by weight, 10-13 parts of dipping solution and 1-2 parts of pigment.

6. A colorful mobile phone back cover based on fiber cloth, characterized in that: Prepared according to the preparation process according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-strength computer rear cover with middle frame and processing technology of high-strength computer rear cover

    CN115403805A

  • Preimpregnated fiber cloth and preparation method therefor

    WO2017016436A1